The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fpls.2014.00114
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities and differences of T3SSs in rhizobia and plant pathogenic bacteria

Abstract: Plant pathogenic bacteria and rhizobia infect higher plants albeit the interactions with their hosts are principally distinct and lead to completely different phenotypic outcomes, either pathogenic or mutualistic, respectively. Bacterial protein delivery to plant host plays an essential role in determining the phenotypic outcome of plant-bacteria interactions. The involvement of type III secretion systems (T3SSs) in mediating animal- and plant-pathogen interactions was discovered in the mid-80's and is now rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 163 publications
(261 reference statements)
1
84
0
Order By: Relevance
“…The ability to induce nodules on NF-independent Aeschynomene species is widespread among Bradyrhizobium species The increasing availability of genome sequences has revealed that the presence of a T3SS is frequent among rhizobia (Tampakaki, 2014). We therefore hypothesized that some strains could be able to exploit this T3SS machinery to develop a more compatible symbiotic relationship with Aeschynomene.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to induce nodules on NF-independent Aeschynomene species is widespread among Bradyrhizobium species The increasing availability of genome sequences has revealed that the presence of a T3SS is frequent among rhizobia (Tampakaki, 2014). We therefore hypothesized that some strains could be able to exploit this T3SS machinery to develop a more compatible symbiotic relationship with Aeschynomene.…”
Section: Resultsmentioning
confidence: 99%
“…The symbiotic T3SS is responsible for the nodulation specificity phenotype shown by several Sinorhizobium fredii and Bradyrhizobium elkanii strains in their symbiosis with certain soybean cultivars (44,45). In these cases, the inactivation of the T3SS allows nodulation.…”
Section: Discussionmentioning
confidence: 99%
“…T3S systems are present in plant- and animal-pathogenic bacteria as well as in several non-pathogenic bacteria and species (spp.) of the symbiotic bacterium Rhizobium , suggesting that T3S is not exclusively linked to pathogenicity (Troisfontaines and Cornelis 2005; Tampakaki 2014). According to phylogenetic analyses, T3S systems from plant-pathogenic bacteria have been grouped into different families including Hrp1 (hypersensitive response and pathogenicity 1; in spp.…”
Section: Introductionmentioning
confidence: 99%